Using the bio-psycho-social-spiritual framework in holistic health and well-being: A case example of a community- and faith-based sports program - Morgan Braganza; Jacob Oliveira (Health for All Nations, 2022)
As in other parts of the world, Canada's citizens are confronted with biological, mental, and social crises. Despite the fact that these issues can be interrelated, they are regularly studied and addressed separately. The bio-psycho-social (BPS) framework was offered as an alternative approach for care because of its assumption that in order to produce a variety of interconnected outcomes relative to health and well-being, biological, mental, and social issues must all be considered. Some authors have argued, however, that without a spiritual component, the BPS framework is not holistic. As such, recent scholarship has explored the inclusion of a spiritual component in the framework, and social service professionals have been encouraged to consider designing interventions informed by the bio-psycho-social-spiritual (BPS-S) framework. Good examples of how to apply the framework in practice are limited. This case example describes how the BPS-S framework was applied to design a community-, sports-, and faith-based martial arts program in Ontario, Canada. The program draws upon a combination of sports-, community-, and Christian faith-based considerations to serve its participants, including vulnerable populations such as those with constrained access to social services due to mental health challenges, language barriers, or low levels of income. This article details some of the ways in which the operations of this program (e.g., activities, target audience, leadership) were informed by the BPS-S framework. This includes some of the advantages of drawing upon this framework to foster more nuanced and holistic well-being among participants. The article concludes with some limitations of the BPS-S framework and implications for applying it to other social service interventions.